Hyperandrogenism due to ovarian steroid cell tumor in a pediatric patient - Del Águila-Villar, Carlos (2024)
Ovarian tumors are rare in pediatrics. In this group, steroid cell tumors represent 0.1% of total cases and there are few reports in the literature. We present the case of an 11-year-old girl who suffered from deeper voice, hirsutism, acne and clitoromegaly. Analysis showed elevated levels of total and free testosterone, normal levels of 17-hydroxyprogesterone. Ultrasound evaluation revealed significant enlargement of the left ovary. The patient underwent left salpingo-oophorectomy. This finding is consistent with an ovarian steroid cell tumor. This is followed by gradual reduction of androgens and clinical improvement. Steroid cell tumors are rare in pediatrics, however, they should be considered as a differential diagnosis when studying patients with symptoms of hyperandrogenism.